Tunable liquid-crystal source of photon pairs - Sultanov, Vitaliy; Kavčič, Aljaž; Kokkinakis, Manolis; Humar, Matjaž; Chekhova, Maria (CLEO: Science and Innovations 2024, 2024)
We demonstrate a liquid-crystal broadband source of entangled photons, whose flux and polarization are tunable through the electric field or molecular twist. This opens a path to a new generation of tunable quantum light sources.
CRIS-Team Scopus Importer:2024-10-04